Cutaneous Allodynia Associated With The Use Of Personal Protective Equipment During The Covid-19 Pandemic - Costa, Camila Vitória De Moraes; Santos, Alisson Sousa; Rêgo, Adriana Sousa; Rabelo, Sarah Tarcisia; Alves, Geovanna Cristina Pereira; Cardoso, Thayllane Costa; Dibai, Daniela Bassi; Gonçalves, Maria Claudia; Paz, Bruna Katarina Beserra (Headache Medicine, 2023)
Full abstract in PDF.